The over expression of thioredoxin during malignancies - Shahaboddin Shabani; Navid Nourizadeh; Mohammadsaleh Soltankhah (Reviews in Clinical Medicine, 2014)
Thioredoxin system comprised of thiorexin and NADPH dependent thiorexin reductase, is responsible for redox regulation of cells by controlling the apoptosis, proliferation and other vital processes of cells. The efficacy of thioredoxin system has been represented in a wide range of physiological and biological reactions in bacteria, yeast, plants, mammals and etc. including DNA synthesis, regulation of transcription factors, protein repairing, regulating the photosynthesis and controlling the apoptosis and preventing oxidative stresses, filamentous phage assembly, immune-modulating, neuronal survival, pregnancy and birth and many other physiological and biological functions. The up-regulation of thioredoxin has been observed in various malignancies, which was associated with tumor angiogenesis and development. In this regard, the thiordoxin system has become a putative target in new chemotherapeutic methods. In this study, we mentioned various features of thioredoxin system in malignant cells and reviewed the articles which have evaluated the expression rate of thioredoxin system in malignancies.